DOWN PAYMENT (DP) NOL RUPIAH DALAM KEPEMILIKAN RUMAH MENURUT HUKUM POSITIF DI INDONESIA - Hulman Panjaitan (Fakultas Hukum Universitas Kristen Indonesia, 2018)
Abstract In accordance with the provisions of the positive law in force, the ownership or acquisition of land with a â€œDP Nol Rupiahâ€ or without Down Payment is possible and legal according to the agreement of the parties which in practice is mostly done individually, but if the buying and selling activities, however, if the sale and purchase of the house is done through a business entity, then according to the rules in effect the down payment or down pay- ment is a must. It is time for the government to formulate a policy as the realization of the government's rights and guarantees for the provision of decent and healthy housing that can be affordable by all levels of society. Keywords: without down payment; legal according; purchase of the house; formulate a policy .